BIG‐BOX RETAILERS, RETAIL EMPLOYMENT, AND WAGES IN THE US. Issue 1 (23rd July 2019) - Peralta, Denis; Kim, Man‐Keun
Abstract : This paper examines the dynamic interrelationship between the presence of big‐box retailers and retail employment and wages in the United States at county level for 1986–2005 using panel vector autoregressions (Panel VAR). The Panel VAR approach addresses endogenous interactions among the variables in the system. In other words, this approach takes into account the fact that the presence of big‐box retailers can have an impact on retail employment and wages and at the same time, retail employment and wages can influence the presence of big‐box retailers. Results indicate that the presence of big‐box retailers has a positive effect on employment but a negative effect on wages. The effect on wages is relatively greater and is more prolonged than the effect on employment. Both employment and wages have an instant (first year) positive effect on the presence of big‐box retailers, which implies that big‐box stores are located in areas where the economy is growing.